Strategies to Produce Cost-Effective Third-Generation Biofuel From Microalgae - Rafa, Nazifa; Ahmed, Shams Forruque; Badruddin, Irfan Anjum; Mofijur, M.; Kamangar, Sarfaraz (Frontiers in Energy Research, 2021)
Third-generation biofuel produced from microalgae is a viable solution to global energy insecurity and climate change. Despite an annual current global algal biomass production of 38 million litres, commercialization confronts significant economic challenges. However, cost minimization strategies, particularly for microalgae cultivation, have largely been excluded from recent studies. Therefore, this review provides essential insights into the technologies and economics of cost minimization strategies for large-scale applications. Cultivation of microalgae through aquafarming, in wastewater, or for biogas upgrading, and co-production of value-added products (VAPs) such as photo-bioreactors, protein, astaxanthin, and exopolysaccharides can drastically reduce biodiesel production costs. For instance, the co-production of photo-bioreactors and astaxanthin can reduce the cost of biodiesel production from $3.90 to $0.54 per litre. Though many technical challenges need to be addressed, the economic analysis reveals that incorporating such cost-effective strategies can make the biorefinery concept feasible and profitable. The cost of producing microalgal biodiesel can be lowered to $0.73kg−1 dry weight when cultivated in wastewater or $0.54L−1 when co-produced with VAPs. Most importantly, access to co-product markets with higher VAPs needs to be encouraged as the global market for microalgae-based VAPs is estimated to rise to $53.43 billion in 2026. Therefore, policies that incentivize research and development, as well as the production and consumption of microalgae-based biodiesel, are important to reduce the large gap in production cost that persists between biodiesel and petroleum diesel.